The parameters of our cage - Cabrera, C. Fausto; Soth, Alec 1969- (Mack, 2020)
In January 2020, Alec Soth received a letter from Chris Fausto Cabrera, an inmate of the Minnesota Correctional Facility in Rush City, in which he asked the photographer to engage in a dialogue. This sparked an expansive and insightful correspondence over the following nine months which, set against the backdrop of the COVID-19 pandemic, Black Lives Matter Movement and growing unrest, reaches to the heart of contemporary America. In amongst their exchanges of personal histories and shared influences – from Ralph Ellison’s The Invisible Man and André 3000, to Robert Frank’s The Americans and Rilke’s 'Letters to a Young Poet' – developed a searing investigation of the redemptive power of art and the imagination, justice and accountability, life inside America’s prisons, and the astonishing capacity of empathy and curiosity to bring two people together. All proceeds from this book will be donated to the Minnesota Prison Writing Workshop [Verlags-Homepage]
Keywords: Cabrera, C. Fausto; Soth, Alec -- 1969-; Geschichte 2020; Geschichte; Fotografie -- Motiv; Porträtfotografie; Alltag; Gefängnis -- Motiv; Briefsammlung; USA